Principles of human joint replacement design and clinical application - Buechel, Fred; Pappas, Michael J.; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book is written for the users and designers of joint replacements. In its second extended edition it conveys to the reader the knowledge accumulated by the authors during their forty year effort on the development of replacement devices for the lower limb for the purpose of aiding the reader in their design and evaluation of joint replacement devices. The early chapters describe the engineering, scientific and medical principles needed for replacement joint evaluation. One must understand the nature and performance of the materials involved and their characteristics in vivo, i.e. the response of the body to implant materials. It is also essential to understand the response of the implants to applied loading and motion, particularly in the hostile physiological environment. A chapter describes the design methodology now required for joint replacement in the USA and EU countries. The remaining chapters provide a history of joint replacement, an evaluation of earlier and current devices and sample case histories of some of the authors? devices. The present second edition includes various additional case reports as well as a new chapter devoted to the shoulder. Drs. Buechel, an orthopaedic surgeon, and Pappas, a professor of Mechanical Engineering, are the designers of several successful joint replacement systems. The most well-known of these is the pioneering LCS knee replacement.
Properties of Materials Used in Orthopaedic Implant Systems -- Failure Modes -- The Design Process -- The Ankle -- The Hip -- The Knee -- The Shoulder.
Electronic reproduction.
Keywords: Arthroplasty; Electronic books